Categories of Analysis and Categories of Practice since the Tajik Civil War - Sophie Roche (Antropologia, 2013)
The paper examines the interplay between analytical categories used by researchers and the practical categories used by ordinary people to understand and navigate their social realities during and after the Tajik Civil War. By focusing on the lived experiences and everyday practices, the study highlights how social categories are constructed and reified through conflict and its aftermath. The research emphasizes the importance of considering local contexts and the perspectives of non-elite actors to gain a comprehensive understanding of societal transformations triggered by civil war.